Bases de datos policiales sobre identificadores obtenidos a partir del ADN y derecho a la intimidad genética - Caruso Fontán, Viviana (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2012)
The use of DNA analysis as expert evidence in a criminal trial and the later incorporation of this information into genetic databases affect both the right to privacy and the right to informational self-determination. In the present work the requirements that these practices must have so that the violation of these fundamental rights is considered proportional to the purposes being pursued and, therefore, legitimate from the constitutional point of view, will be analyzed.